What makes them tick - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Taxonomy of African Ticks. An Identification Manual By J Okello-Onen, S M Hassan & S Essuman, ICIPE, 1999. 125 pp. ISBN 92 9064 127 4 US$ 35 Euro 39.70 , for African institutions, US$ 45 Euro 51 for others